2012
DOI: 10.1159/000338241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Phacoemulsification and Viscogoniosynechialysis versus Trabeculectomy in Patients with Primary Angle-Closure Glaucoma and Coexisting Cataract

Abstract: Aims: To compare the effectiveness of combined phacoemulsification and viscogoniosynechialysis versus trabeculectomy alone in primary angle-closure glaucoma (PACG) with a coexisting cataract. Methods: Thirty-nine Chinese patients (39 eyes) were retrospectively analyzed: 19 patients underwent combined phacoemulsification and viscogoniosynechialysis (group 1), and 20 underwent trabeculectomy (group 2). In both groups, the intraocular pressure (IOP), the number of antiglaucoma medications, the best corrected visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…20 literary works from 2011 to 2022 were eventually included in the meta-analysis, as follows: Guoying Liu 2017 [16], Siyi Zhang 2016 [17], Zhaorong Zeng 2013 [18], Zaifang Wang 2019 [19], Kun Wang 2019 [20], Jili Chen 2017 [21], Canhua Huang 2019 [22], Ayinuer 2015 [23], Tang Y 2012 [24], Zhang H 2016 [12], Yanjun Huang 2011 [25], Kai Ma 2015 [26], Tian Yang 2019 [27], Lianrong Su 2013 [28], Ning Ma 2018 [29], Chaohua Huang 2018 [30], Yufei Cai 2021 [31], Qingzhi Wang 2020 [32], Shuifeng Deng 2021 [33], Yongqiang Liang 2013 [34]. Figure 1 depicts the literature screening procedure.…”
Section: Search Resultsmentioning
confidence: 99%
“…20 literary works from 2011 to 2022 were eventually included in the meta-analysis, as follows: Guoying Liu 2017 [16], Siyi Zhang 2016 [17], Zhaorong Zeng 2013 [18], Zaifang Wang 2019 [19], Kun Wang 2019 [20], Jili Chen 2017 [21], Canhua Huang 2019 [22], Ayinuer 2015 [23], Tang Y 2012 [24], Zhang H 2016 [12], Yanjun Huang 2011 [25], Kai Ma 2015 [26], Tian Yang 2019 [27], Lianrong Su 2013 [28], Ning Ma 2018 [29], Chaohua Huang 2018 [30], Yufei Cai 2021 [31], Qingzhi Wang 2020 [32], Shuifeng Deng 2021 [33], Yongqiang Liang 2013 [34]. Figure 1 depicts the literature screening procedure.…”
Section: Search Resultsmentioning
confidence: 99%
“…Tang et al retrospectively compared the effectiveness of combined phacoemulsification and viscogoniosynechia-lysis (phaco-GSL) with trabeculectomy alone in PACG with coexisting cataract [ 28 ]. They analyzed 19 patients who underwent phaco-GSL and 20 patients who underwent trabeculectomy.…”
Section: Lens Extraction As Subsequent Treatment After Peripheral Irimentioning
confidence: 99%
“…5 Intraocular lens surgery was not performed simultaneously in each patient. Briefly, trabeculectomy was performed under peribulbar anesthesia.…”
Section: Surgical Trabeculectomy Proceduresmentioning
confidence: 99%
“…3 In addition, previous reports have suggested that canaloplasty, a procedure involving circumferential viscodilation and tensioning of Schlemm's canal, achieved a significant decrease in IOP at 12 months and the IOP decrease is sustained in adult patients with open-angle glaucoma. [4][5][6] Since trabeculectomy could significantly decrease the IOP in PACG eyes, this surgical treatment could result in changes in the SC. However, the features of SC morphology in PACG eyes undergoing trabeculectomy are still unknown.…”
mentioning
confidence: 99%